Virtual Objective Structured Clinical Examinations for Independent and Supplementary Prescribing Trainees: redeveloping a high‐stakes assessment. (18th March 2022) - Kennedy, Mary‐Claire; Dickinson, Rebecca; Alldred, David; Bradbury, Helen; Easthall, Claire; Greer, Dan; Shaffiq, Sumrah; Strickland‐Hodge, Barry
Abstract: The Independent and Supplementary Prescribing programme has been offered by the University of Leeds since 2002. Upon completion of the programme pharmacists, nurses, midwives, physiotherapists, and paramedics register as prescribers with their professional regulator. Trainees attend teaching sessions over a 3‐month period followed by a period of supervision in practice. All trainees undertook an objective structured clinical examination (OSCE) at the end of the 3‐month period. Usually, the OSCE takes place on the university campus over one day. With the onset of the COVID‐19 pandemic, the OSCE had to be restructured so that it could take place virtually, while maintaining the validity and reliability of the assessment. Microsoft Teams ® was identified as the most appropriate platform for conducting the Virtual‐OSCE (V‐OSCE). Overall, the V‐OSCEs we ran were a success; trainees, assessors and simulated patients reported that the assessment was seamless. However, further improvements could be made to improve the efficiency of the process if this approach were to become commonplace within the programme.